2016
DOI: 10.1139/cgj-2015-0122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas bubbles on pore pressure response in peat beneath a railway embankment

Abstract: This paper presents the pore pressure behaviour observed within peat beneath a newly constructed railway embankment. Piezometers installed at different depths beneath the structure showed episodic increases in pore pressure above hydrostatic pressure followed by a rapid pore pressure decrease. It was postulated that this fluctuation in pore pressure was due to the movement and expulsion of gases within the peat. Investigations were conducted in the laboratory to replicate this pore pressure response. The peat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Through an extensive literature review Kaminski et al (2020) point out the mechanisms by which gas exsolution and subsequent accumulation of bubbles can affect the stability of submarine slopes. The results of the present study add to the rare in situ evidences that free gas migration and accumulation in shallow, fine-grained sediments or peat are associated with transient overpressures (Acharya et al, 2016;Bennett et al, 1996;Tjelta et al, 2007). Because the development of overpressures decreases the effective stress and in turn the resistance to failure (e.g., Stigall & Dugan, 2010), it is worth stressing that λ* locally exceeds 0.3 in types 2 and 3 FGOs.…”
Section: Geohazard Implicationssupporting
confidence: 76%
See 2 more Smart Citations
“…Through an extensive literature review Kaminski et al (2020) point out the mechanisms by which gas exsolution and subsequent accumulation of bubbles can affect the stability of submarine slopes. The results of the present study add to the rare in situ evidences that free gas migration and accumulation in shallow, fine-grained sediments or peat are associated with transient overpressures (Acharya et al, 2016;Bennett et al, 1996;Tjelta et al, 2007). Because the development of overpressures decreases the effective stress and in turn the resistance to failure (e.g., Stigall & Dugan, 2010), it is worth stressing that λ* locally exceeds 0.3 in types 2 and 3 FGOs.…”
Section: Geohazard Implicationssupporting
confidence: 76%
“…Distinguishing between the signatures of these two processes will be the topic of a dedicated study. Meanwhile, it is interesting to note that at the type 3 FGO location n g appears to scale with the ultimate peak pressure of sawtooth cycles which Acharya et al (2016) and Rocco et al (2017) experimentally identified as the "escape pressure" or "fracturing pressure." To gain some sense of the magnitude of these ultimate peak pressures in the study area, they have been normalized to the hydrostatic effective stress, providing overpressure ratios in the 0.27 < λ* < 0.45 range.…”
Section: Distribution Of Free Gas In Sediment and Underlying Controlsmentioning
confidence: 98%
See 1 more Smart Citation
“…Luxurious nZVI may give rise to a hardened soil, making it difficult to drain under the consolidation pressure of 200 kPa and thus contributing to an exceptionally high moisture retaining capacity (Burgess et al, 2016). Furthermore, with regard to the microbubbles and their bubble prints in the soil samples, the presumption was that these micron-level bubble-prints were the residual channeled network of voids for the drainage boundary (Acharya et al, 2015). However, the density and porosity of nZVI-treated soil decreased synchronously.…”
Section: Undrained Shear Strengthmentioning
confidence: 99%
“…Only few contributions dealt with the possible geotechnical impact of gas in peats with reference to the structural response of dykes or railway embankments (Vonk, 1994;Den Accepted manuscript doi: 10.1680/jgeot.17.P.148 Haan & Kruse, 2007;Acharya et al, 2016aAcharya et al, , 2016b. However, all these contributions just highlighted that local overpressure may occur due to gas pockets, but none of them included a systematic study on the consequences of gas entrapment on the mechanical behaviour of peats.…”
Section: Introductionmentioning
confidence: 99%